2008
DOI: 10.1016/j.jtcvs.2008.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The morphologic left ventricle that requires training by means of pulmonary artery banding before the double-switch procedure for congenitally corrected transposition of the great arteries is at risk of late dysfunction

Abstract: The early results of the double-switch procedure in patients whose morphologic left ventricle required training compare favorably with those of patients whose morphologic left ventricle required no training. There is an increased risk of deterioration of morphologic left ventricle function over time in patients whose morphologic left ventricle requires training, and these patients need to be followed up regularly to detect this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 31 publications
(38 reference statements)
2
48
2
Order By: Relevance
“…The incidence of late LV dysfunction is up to 20% in midterm follow-up, with a constant need for heart transplant. The negative impact of complete heart block, progressive aortic regurgitation, the need for retraining the LV, especially in older patients, and intraventricular tunnel obstruction, on the long-term function of the LV, are well documented [5,6,15]. Our data demonstrate the preservation of normal left ventricular function after correction, even in patients who required LV retraining.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The incidence of late LV dysfunction is up to 20% in midterm follow-up, with a constant need for heart transplant. The negative impact of complete heart block, progressive aortic regurgitation, the need for retraining the LV, especially in older patients, and intraventricular tunnel obstruction, on the long-term function of the LV, are well documented [5,6,15]. Our data demonstrate the preservation of normal left ventricular function after correction, even in patients who required LV retraining.…”
Section: Discussionsupporting
confidence: 55%
“…A ratio of leftto-right ventricular systolic pressure of 0.8, in the presence of a well-preserved LV function, with the indexed LV mass to LV volume ratio >1.5, is considered to be adequate for anatomical correction [13]. Quinn et al [15] demonstrated that up to 50% of patients who underwent LV training before anatomic repair had moderate-to-severe LV dysfunction at intermediate follow-up, compared with a prevalence of 20% in patients who did not require training. In our series, four patients underwent PAB for retraining the LV.…”
Section: Issues Related To Asomentioning
confidence: 99%
“…It could be postulated that either relocation of the (morphologically) left ventricle in the systemic position or cardiac transplantation is the surgical treatment of choice in these cases; however, results after relocation of the left ventricle into the systemic position, in terms of survival and benefit, are discouraging in the adult population with transposition of the great arteries. 28,29 The option of cardiac transplantation is probably the superior option from a functional point of view. Unfortunately, donor organs are scarce, and cardiac transplantation can only be applied in a limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Quinn et al showed that patients requiring LV retraining prior to anatomical repair may be more at risk of developing significant LV dysfunction than patients whose MLV remains at systemic pressure at birth. 15 Furthermore, some large studies also showed that some patients who met the criteria died or underwent heart transplantation due to severe LV dysfunction after anatomical repair (Table 1). 7,8 In fact, the latest follow-up echocardiography showed a mild decrease in MLV ejection fraction in the present case.…”
Section: Discussionmentioning
confidence: 99%